2010
DOI: 10.1007/s12105-009-0159-5
|View full text |Cite
|
Sign up to set email alerts
|

Low Grade Glandular Lesions of the Sinonasal Tract: A Focused Review

Abstract: The sinonasal tract is a complex anatomic site with an exhaustive list of possible diagnoses. While most biopsies or resections encountered routinely consist of common diagnoses such as inflammatory polyps and papillomas, occasional cases are more difficult, and separating reactive or benign from malignancy can be challenging. One of the most poorly understood and daunting categories is low grade glandular or tubular proliferations, particularly on small biopsies. Possible diagnoses such as reactive lesions, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…Weinreb [19], in a recent review of low grade glandular lesions of the sinonasal tract, comments that the typical features of both REAH and seromucinous hamartoma can focally be seen within inflammatory lesions as well as within normal sinonasal mucosa. He also observed that these foci can have inconsistent myoepithelial staining.…”
Section: Discussionmentioning
confidence: 99%
“…Weinreb [19], in a recent review of low grade glandular lesions of the sinonasal tract, comments that the typical features of both REAH and seromucinous hamartoma can focally be seen within inflammatory lesions as well as within normal sinonasal mucosa. He also observed that these foci can have inconsistent myoepithelial staining.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelium is bland and mature, although uncommonly one can see attenuated epithelium that appears collapsed (atrophic). Focal hyperplasia of the adjacent seromucinous glands [19], a typical finding of SH, may also be present. This is a common overlapping feature between REAH and SH, in addition to their common origins in the posterior nasal cavity and septum.…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of SH show localized REAH like changes with glands and cysts lined by invaginated respiratory epithelium, although this is usually only focal [15]. Similarly, many cases of REAH show seromucinous glands [19]. As such, they may simply represent a continuum of changes that have been somewhat arbitrarily divided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations